Development of C&I for tropical plantation forests - Hopmans, P.; Prabhu, Ravi; Brand, D.; Nambiar, S.; Cossalter, C. (1998)
Tropical countries are expanding plantation forestry to develop sustainable wood production systems. Much of this is based on short rotations of exotic species. These systems require large capital investments, represent intensive land use and increase the demands on the soil. To develop options for maintaining or increasing productivity, a partner-project was initiated by Center for International Forestry Research (CIFOR) with three objectives: 1) evaluate the impact of soil and site management practices on the productivity of successive rotations of plantations, 2) develop management options for maintaining or increasing productivity and 3) where it is appropriate strengthen local institutional capacity to respond to new problems and opportunities. The project focuses on the critical inter-rotational phase of management: harvesting, site preparation, and early stand developement. A core set of treatments selected to create a range of impacts on organic matter and nutrients supply intensities will be included at all locations. Optional treatments tailored to each site will be added as required by local management, and soil and stand considerations. Each location will carry out a self-contained experiment that will produce scientifically valid results on its own merit. All experiments are networked to integrate the information so underlying processes can be understood and options for science based management developed. All sites are expected to be valuable reference sites for long-term investigations.